Pembelajaran Fisika Menggunakan Model Problem Based Learningdan Project Based Learning Ditinjau dari Keterampilan Proses Sains Siswa padaMateri Fluida Statis di Kelas XI SMA Panca Bhakti Pontianak - Siti Halijah; Handy Darmawan (JURNAL PENDIDIKAN SAINS DAN APLIKASINYA, 2019)
The purpose of this study was to determine the learning outcomes of physics learning using the Problem Based Learningmodel and the Project Based Learning model in terms of the science process skills of students on static fluid material in class XI of SMA Panca Bhakti Pontianak. The method used in this study was an experimental method with a 2 x 3 factorial design. The population in this study was a class XI student at Panca Bhakti High School Pontianak which consisted of two classes. Based on the sampling technique with cluster random sampling obtained XI IPA 1 class as experimental class one and XI IPA 2 as experimental class two. Data collection techniques used were measurement techniques with essay tests. Based on the analysis of the data obtained the average student learning outcomes on static fluid material that is applied to the Problem Based Learningmodel that is 76.52 and that is applied to the Project Based Learning model that is 79.00. The science process skills of students in the static fluid material applied by the Problem Based Learningmodel are 38.62 and that of the Project Based Learning model is 34.76. Based on the results of data analysis using the two-way Kruskal Wallis anova test for students' science process skills P-value is obtained 0,000 0.05, so Ha is accepted and the results of the two-way Kruskal Wallis anova test calculation for the learning model that is there is an influence with P-value 0,000 0.05 so that Ha is accepted and there is an interaction between the Problem Based Learningmodel and the Project Based Learning model of the science process skills and the learning outcomes.